A Practitioner’s Guide to Stochastic Frontier Analysis Using STATA - Rangkakulnuwat, Poomthan (Asian Journal of Applied Economics, 2017)
This book is excellent in explanation of technical efficiency measurement by stochastic frontier analysis. This book enables readers to understand how technical efficiency is computed and interpreted. Each chapter starts with a theoretical of stochastic frontier model followed by examples of applying the theory to real data. Data and STATA syntax of all examples are downloadable from website. This ensures that practitioners can apply these tools to their research.